Colonization resistance against multi-drug-resistant bacteria: a narrative review. (December 2021) - Le Guern, R.; Stabler, S.; Gosset, P.; Pichavant, M.; Grandjean, T.; Faure, E.; Karaca, Y.; Faure, K.; Kipnis, E.; Dessein, R.
Summary: Colonization resistance by gut microbiota is a fundamental phenomenon in infection prevention and control. Hospitalized patients may be exposed to multi-drug-resistant bacteria when hand hygiene compliance among healthcare workers is not adequate. An additional layer of defence is provided by the healthy gut microbiota, which helps clear the exogenous bacteria and acts as a safety net when hand hygiene procedures are not followed. This narrative review focuses on the role of the gut microbiota in colonization resistance against multi-drug-resistant bacteria, and its implications for infection control. The review discusses the underlying mechanisms of colonization resistance (direct or indirect), the concept of resilience of the gut microbiota, the link between the antimicrobial spectrum and gut dysbiosis, and possible therapeutic strategies. Antimicrobial stewardship is crucial to maximize the effects of colonization resistance. Avoiding unnecessary antimicrobial therapy, shortening the antimicrobial duration as much as possible, and favouring antibiotics with low anti-anaerobe activity may decrease the acquisition and expansion of multi-drug-resistant bacteria. Even after antimicrobial therapy, the resilience of the gut microbiota often occurs spontaneously. Spontaneous resilience explains the existence of a window of opportunity for colonization of multi-drug-resistant bacteria during or just after antimicrobial therapy. Strategies favouring resilience of the gut microbiota, such as high-fibre diets or precision probiotics, should be evaluated.